Aligning sentence structures in dialogue: evidence from aphasia. Issue 6 (3rd July 2019) - Lee, Jiyeon; Man, Grace; Ferreira, Victor; Gruberg, Nicholas
ABSTRACT: Syntactic alignment in dialogue is pervasive and enduring in unimpaired speakers, facilitating language processing and learning. Recent work suggests that syntactic alignment extends to the level of event-semantic properties ( syntactic entrainment ). Two experiments examined whether syntactic entrainment can ameliorate impaired message-structure mapping in persons with aphasia (PWA). In Experiment 1, participants first heard twelve picture descriptions, each using one of two suitable syntactic structures, prior to describing the same twelve pictures themselves. In Experiment 2, participants also repeated the heard picture descriptions, thereby increasing the depth of encoding for prime sentences. PWA showed a robust tendency to re-use previously encountered syntactic structures in their own production only in Experiment 2. They produced fewer "mapping" errors (e.g. thematic role reversals) in Experiment 2 than in Experiment 1. Syntactic entrainment remains resilient in aphasia, strengthening their event-semantic-to-syntax mappings, at least when active encoding of prior message-syntax associations is ensured.